Antecedents of Intention to Use Green Banking Services in India1. (23rd September 2016) - Bryson, Douglas; Atwal, Glyn; Chaudhuri, Anindita; Dave, Kartik
Abstract : Banks in India face opportunities to innovate to meet changing expectations regarding green banking practices.